Research on Blockchain in Supply Chain Finance Risk Management - Guo, Shenglan (Transactions on Economics, Business and Management Research, 2023)
With the development of supply chain finance, the business process of supply chain finance is more complex, and the participants are more diversified, bringing new risks to supply chain finance. Based on studying the risk sources and types of supply chain finance, combined with the core technology of blockchain and taking the blockchain + supply chain finance accounts receivable financing mode as an example, this paper proposes that blockchain can solve the problem of information asymmetry by reshaping the information flow of supply chain finance, breaking down information barriers, improving the credibility and transparency of information and expanding the scope of credit through smart contracts and distributed ledger technologies. In addition, financial institutions can reduce moral hazards and review costs caused by human operations through the characteristic advantages of blockchain consensus mechanism and traceability and ensure the authenticity and security of transaction information through the asymmetric key method and sharing mechanism of blockchain.